Algae as a source of protein in the sustainable food and gastronomy industry - Procházka, Petr; Abrham, Josef; Cerveny, Jaroslav; Soukupová, Jana; Ouma, Christine Nabwire; Mullen, Kevin Jan; Sanova, Petra; Smutka, Lubos (Frontiers in Sustainable Food Systems, 2023)
The paper aims to examine the prospects of algae production as a source of protein in the European market. As well as highlighting the promising developments in the algae food industry in Europe. By 2027, it is expected that the algae protein market will be worth approximately USD 300 million. To fully utilize algae as a source of protein, however, a number of technological, regulatory, and marketrelated obstacles must be resolved despite the indicative advantages. Developing cost-effective and efficient methods for algae cultivation, harvesting, and processing are also necessary. Uniform and consistent regulations are needed to guarantee the safety and quality of products that contain algae, as well as consumer awareness campaigns and education about the advantages of algae protein. In addition to providing evidence of the viability of algae production as a source of food, this study demonstrates that algae land needs are negligible compared to other protein sources -animal-based like pork, chicken and beef production but also plant-based alternatives such as nuts, pulses, grains and peas.. Specifically, algae need 2.5 m 2 of land per kilogram of protein as opposed to 47-64 m 2 for pork production, 42-52 m 2 for chicken production while the highest land need is 144-258 m 2 required for beef production. Furthermore, results in this study may inspire a more targeted focus on algae production as a source of nutrition and inspire more organizations in Europe to collaborate with the EU4 Algae platform.around the world to move ahead with the alternative protein source production from algae.